Singing reconciliation: inhabiting the moral life according to Colossians 3:16 - Krall, Amy Whisenand ca. 21. Jhd. (Biblical interpretation series, 2023)
This study shows how singing in Colossians 3:16, as a corporate, vocal practice of music-making, enables the members of the church community to inhabit the story of reconciliation found in the Christ Hymn (Col 1:15-20).